Exploring Language Ideology and Religious Identity: Strategies for Teaching English in Boarding School Setting - Elga Romadhon, M Galuh (UHN IGB Sugriwa Denpasar, 2024)
The integration of English language pedagogy in Islamic boarding schools serves several purposes. This study aims to explore how ideological perspectives on English intersect with religious and cultural norms within Islamic educational settings, examining challenges such as reconciling Islamic doctrines with Western influences and integrating religious values into language learning. The researcher employed a qualitative methodology to capture the profoundness and intricacy of the participants' experiences, beliefs, and practices pertaining to English language learning in Islamic schools. The research methodology encompassed a purposive sampling technique to select participants. A semi-structured interview model was utilized to explore the information provided. The researchers organized the results obtained from the interview data into three main themes: Managing the intersection of language, culture, and faith; addressing obstacles linked to integrating faith into the educational journey; and adapting approaches for different stages of boarding school education. The results shed light on the diverse tactics employed by students to navigate the educational landscape with sensitivity and discernment, creating an inclusive learning environment that supports the overall development of students. Furthermore, the integration of Islamic principles and cultural heritage played a crucial role in enhancing linguistic fluency and strengthening religious identity among students.